Upaya Meningkatkan Kecerdasan Kinestetik Melalui Senam Irama Pada Anak Kelompok B TK Patisah Pajang Kecamatan Laweyan Kota Surakarta Tahun Ajaran 2014 /2015 - Paslandika, Erni, Dra. Surtikanti, S.H., M.Pd (2015)
Rhytmic Gymnastics is an activity that caught the attention of children and provide a pleasant atmosphere for young children to learn some vital lessons develop kinesthetic intelligence. Factually, many kindergarten teachers are using this methods not optimally yet. Children only see examples of gymnastic movements without giving out the opportunity to go forward and perfom gymnastic movements themselves. The purpose of this rearch is to increase the kinesthetic intelligence of children at Patisah Kindergarten Pajang Laweyan Surakarta in 2014 / 2015 Academic Year. The research is a Classroom Action Research (PTK) with two cycle swork process consists of four stages; planning, action, observation, and reflection. The subjects were children and 15 kingdergarten children in group B Patisah Kindergarten. The result of this reseafch show that the method of demonstration rhythmic gymnastics can icrease kinesthetic intelligence children. The study states that the method of demonstration that rhythmic gymnastics can improve children's intelligence kinestetic. Increase in the average percentage of children kinesthetic intelligence before the action until the second cycle is ; precycle 50,75%, first cycle 63,95%, and the second cycle 87,50%. The conclution was that there was an increase kinesthetic intelligence trough the method of rytmic gymnastic demonstration in kindergarten Patisah Pajang Laweyan Surakarta Academic Year 2014 / 2015. Key word : kinesthetic intelligence, rhythmic gymnastic events.